2017
DOI: 10.2174/1570159x14666160422110344
|View full text |Cite
|
Sign up to set email alerts
|

Positive Emotional Learning Induces Resilience to Depression: A Role for NMDA Receptor-mediated Synaptic Plasticity

Abstract: Background: Positive emotions have been shown to induce resilience to depression and anxiety in humans, as well as increase cognitive abilities (learning, memory and problem solving) and improve overall health. In rats, frequency modulated 50-kHz ultrasonic vocalizations (Hedonic 50-kHz USVs) reflect a positive affective state and are best elicited by rough-and-tumble play.Methods: The effect of positive affect induced by rough-and tumble play was examined on models of depression and learning and memory. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 88 publications
0
16
0
1
Order By: Relevance
“…This plasticity of the brain in adult life is strikingly demonstrated by the observation that rough-and-tumble play facilitates positive emotional learning and induces resilience to depression in late-adolescent (adult) rats (Burgdorf et al, 2017). Interestingly, studies further solidify this concept by demonstrating that for an increased brain plasticity to occur, play with toys used in the experiment must occur with other rats in a playful social interaction as opposed to individually (Burgdorf et al, 2017;Diamond et al, 1987;Diamond, Krech, & Rosenzweig, 1964;Diamond, 1988).…”
Section: Social Intelligencementioning
confidence: 94%
See 2 more Smart Citations
“…This plasticity of the brain in adult life is strikingly demonstrated by the observation that rough-and-tumble play facilitates positive emotional learning and induces resilience to depression in late-adolescent (adult) rats (Burgdorf et al, 2017). Interestingly, studies further solidify this concept by demonstrating that for an increased brain plasticity to occur, play with toys used in the experiment must occur with other rats in a playful social interaction as opposed to individually (Burgdorf et al, 2017;Diamond et al, 1987;Diamond, Krech, & Rosenzweig, 1964;Diamond, 1988).…”
Section: Social Intelligencementioning
confidence: 94%
“…rat laugher (Liu et al, 2017;Hirsh-Pasek et al, 2009;Whitton, 2018;Yogman et al, 2018). Extraordinarily, rough-and-tumble play in rats (a playful activity in which rats engage well into their adulthood) induces excessive laughter, which can lead to resilience against depression and anxiety, and facilitation of learning and memory (Burgdorf, Colechio, Stanton, & Panksepp, 2017). These effects are mediated, in part, by increased plasticity in the medial prefrontal cortex (Burgdorf et al, 2017;Panksepp, 2005).…”
Section: Physical and Mental Resiliencementioning
confidence: 99%
See 1 more Smart Citation
“…Also, the neurochemistries of positive social affects, as generated normally by PLAY interactions (Burgdorf et al, 2007), should diminish the psychological pain of depression (Burgdorf et al, 2016(Burgdorf et al, , 2011Panksepp, 2015a;. Likewise, in treatment resistant depression, perhaps an optimal target for DBS therapy would be the enthusiasm/interest generating SEEKING urge (Coenen et al, 2012;Panksepp and Yovell, 2014), another predictions that has been confirmed (Schlaepfer et al, 2013).…”
Section: A Critique Of the Cn Perspective (By Jp And Ms)mentioning
confidence: 97%
“…Indeed, because of such ethical concerns, JP decided to devote practically all his research effort for the past three decades to the study of positive emotions, especially animal play and "laughter," and specifically focusing on how such work may help identify new psychiatric treatments (Burgdorf et al, 2016;Panksepp and Wright, 2012;Panksepp and Yovell, 2014;Panksepp, 2016Panksepp, , 2015aWright and Panksepp, 2012;Yovell et al, 2015).…”
Section: #2 What Do the Terms "Raw Subjective Feeling" And "Cognitivmentioning
confidence: 99%